2018
DOI: 10.1093/aje/kwx377
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke and Women’s Cognitive Function in China

Abstract: Exposure to secondhand smoke (SHS) is known to be harmful to health. However, the association between household SHS and cognitive function among middle-aged and older women in China is understudied. Lagged dependent variable regression was used to examine the association between household SHS exposure and the cognitive function of married women who had been exposed to SHS, using data from 2 waves of the China Health and Retirement Longitudinal Study (CHARLS, 2011-2013). Controlling for age, educational attainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…One study indicated that in women aged 55–64 years, second-hand smoke exposure was associated with more memory deterioration and the risk increased with exposure duration even after controlling for other confounding factors. 115 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…One study indicated that in women aged 55–64 years, second-hand smoke exposure was associated with more memory deterioration and the risk increased with exposure duration even after controlling for other confounding factors. 115 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…McArdle et al (2007)'s study of the HRS data suggested two factors to adequately capture cognitive function (McArdle, Fisher, & Kadlec, 2007). Following McArdle et al and based upon previous studies using the CHARLS data(Lei, Hu, McArdle, Smith, & Zhao, 2012;Pan, Luo, &…”
mentioning
confidence: 99%
“…This study builds on previous findings that SHS was associated with poor cognitive performance, especially in children, adolescents and adults. 17 We found that having a high educational level, living in an urban area and having better baseline cognitive function would improve their cognitive performance. The episodic memory score of participants with diabetes at baseline decreased by 0.172 points compared with those without diabetes, which is similar to previous findings.…”
Section: Discussionmentioning
confidence: 74%
“…21 Another longitudinal ageing study in China on those aged ≥50 years (N=4809) found that never-smokers exposed to the highest levels of SHS (salivary cotinine concentrations of 0.8-13.5 ng/mL) were more likely to be cognitively impaired (OR=1.70) than those exposed to little or no SHS. 17 Attention, which referred to the ability to concentrate and focus on specific stimuli, slightly declined in later life. 12 Orientation was one's ability to identify the exact date, month, day and season of the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation